Zipping and Unzipping of a Paddlewheel Metal–Organic Framework to Enable Two‐Step Synthetic and Structural Transformation. Issue 11 (11th February 2013) - Smart, Paul; Mason, Charles A.; Loader, Jason R.; Meijer, Anthony J. H. M.; Florence, Alastair J.; Shankland, Kenneth; Fletcher, Ashleigh J.; Thompson, Stephen P.; Brunelli, Michela; Hill, Adrian H.; Brammer, Lee
<x xml:space="preserve">Abstract</x> MOF zipper: Thermal removal of axial pyridine ligands from the non‐covalently pillared metal–organic framework [Zn2(camph)2(py)2]⋅2EtOH prompts migration of alternate camphorate ligands to zip Zn centers from adjacent layers into continuous chains within the nonporous material [Zn2(camph)2] (see scheme). Unzipping to generate new pillared, layered MOFs occurs on exposure to new axial ligands.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>